Burst Spinal Cord Stimulation: A Systematic Review and Pooled Analysis of Real-World Evidence and Outcomes Data. (1st June 2019) - Chakravarthy, Krishnan; Malayil, Rudy; Kirketeig, Terje; Deer, Timothy
Abstract: Objective: This review provides a comprehensive assessment of the effectiveness of burst spinal cord stimulation (SCS). Ratings of pain intensity (visual analog scale or numeric rating scale) and patient-reported outcomes (PROs) on functional/psychometric domains such as depression (Beck Depression Index), catastrophizing (Pain Catastrophizing Scale), surveillance (Pain Vigilance and Attention Questionnaire), and others are addressed. Design: Articles were identified and selected from the literature according to prospective, replicable methods. Effectiveness data—pain scores and PRO ratings—were weighted by study sample sizes and pooled. The effects of burst SCS were compared against values at baseline and with tonic SCS. For PROs, published population norms were used for comparison. Results: Fifteen articles, with a combined sample size of 427, were included. Follow-up ranged from a few hours to two years. A variety of prospective designs were employed, including crossover studies, single-arm cohorts, and a randomized controlled trial, as well as retrospective case reports. The weighted pooled mean pain rating across articles at baseline was 76.7 (±27.4). With tonic SCS, this was reduced to 49.2 (±12.9), and with burst SCS it was further reduced to 36.7 (±11.6), a 12.5-point difference between tonic and burst values. Psychometric analyses of PROs noted preferential improvement with burst SCS. In addition, 65% of subjects stated a preference for burst SCS. Conclusions: In pooled analyses that incorporated all available published evidence, the improvement over baseline for burst SCS was shown to have a clinically important incremental benefit over tonic SCS. In addition, burst SCS may support resolution of the emotional or cognitive aspects of pain that are mediated by medial thalamo-cortical pathways. This study highlights the value in considering the entire knowledge base in therapeutic assessments as well as adopting a consistent set of outcome variables within neuromodulation. Burst SCS is a valuable intervention, providing both analgesia and psychometric benefits that warrant further thoughtful applications.